Effects of a health literacy program on COVID-19 awareness and preventive behaviors among older adults in Bangkok, Thailand: a quasi-experimental study - Walaya Tupanich; Sasawan Attaworakun; Suteekarn Chaiyalap; Nattanan Wattanawikan (Journal of Korean Academy of Nursing, 2026)
Purpose: This study examined the effectiveness of a health literacy (HL) enhancement program in improving awareness of and preventive behaviors related to coronavirus disease 2019 (COVID-19) among older adults in an urban community in Bangkok, Thailand.Methods: This quasi-experimental study included 76 older adults in Dusit District, Bangkok. Eight participants were lost to follow-up; however, all 76 participants (38 per group) were included in the primary analysis using all available observations. The intervention was based on Pengjuntr’s V-shape HL model, which includes six domains: access, understanding, interactive communication, decision-making, behavior change, and advocacy. The program was delivered through group sessions, LINE-based communication, community activities, and home visits. Data were collected at pre-test (baseline), post-test (4 weeks), and follow-up (12 weeks) using questionnaires. Outcomes were analyzed using linear mixed-effects models. This study was retrospectively registered with the Thai Clinical Trials Registry (TCTR20260502013).Results: At post-test, the experimental group had significantly higher COVID-19 awareness and preventive behavior scores than the control group (p